2020
DOI: 10.1177/0885328220975570
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid coated ultrasmall superparamagnetic iron oxide nanoparticles conjugated with lactoferrin for targeted negative MR imaging of glioma

Abstract: The proposed study was to develop the preparation of ultrasmall superparamagnetic iron oxide nanoparticles (USPIONs) modified with citric acid, with surface conjugated with lactoferrin (Lf), which used as a potential targeted contrast agent for magnetic resonance imaging (MRI) of brain glioma. USPIONs were prepared by the thermal decomposition method. The hydrophobic USPIONs were coated with citric acid by the ligand exchange method. Then, Lf was conjugated into the surface of USPIONs. The obtained Lf-USPIONs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The surface of USPIO with iron acetylacetonate as precursor is coated with polyols, which is not easy to be further modified [ 25 ]. With ferric chloride as precursor, small molecules or macromolecules containing carboxyl, amino and other compounds can be added to obtain USPIO with different surface coating, which is more widely used [ 26 ]. The thermal stability of materials is one of the indicators to select the performance of materials [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surface of USPIO with iron acetylacetonate as precursor is coated with polyols, which is not easy to be further modified [ 25 ]. With ferric chloride as precursor, small molecules or macromolecules containing carboxyl, amino and other compounds can be added to obtain USPIO with different surface coating, which is more widely used [ 26 ]. The thermal stability of materials is one of the indicators to select the performance of materials [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential important role of SPIONs in therapy of GBM results from their ability to exhibit superparamagnetism, which allows them to accumulate at the targeted cancerous tissue when subjected to a magnetic field [ 166 ]. Therefore, SPIONs can be implemented as an effective contrast agent in MRI and may also be important diagnostic tools for the assessment of the grade of the tumor (e.g., evaluation of MRI signal intensities after the administration of probes containing neuropilin-1 and ultra-small SPIONs) [ 167 , 168 ].…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%
“…It was recently reported that the properties of USPIOs could be enhanced by modification with citric acid and subsequent conjugation with lactoferrin. These improved polygonal USPIOs exhibited satisfactory distribution and biocompatibility in numerous studies, including cytotoxicity, migration and blood biochemistry analyses [ 168 ]. PEGylated USPIOs may also be conjugated with Ang-2, which promotes their passage across the BBB, allowing the nanoprobe to be delivered to GBM and improve positive contrast in MRI.…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%
“…The-OH of PEG can provide a polymerization reaction with the active site, and the reaction product is a block copolymer. Additionally, the hydrophilic block of PEG was introduced into the PLLA chain segment to prevent non-specific phagocytosis [23,24].…”
Section: Introductionmentioning
confidence: 99%